Changes in performance and bacterial communities in a continuous biohydrogen-producing reactor subjected to substrate- and pH-induced perturbations. (January 2020) - García-Depraect, Octavio; Diaz-Cruces, Víctor F.; Rene, Eldon R.; León-Becerril, Elizabeth
Highlights: Hydraulic retention times (HRTs) lower than 12 h boosted the production of H2 . The reactor recovered from all perturbances enabling high-rate H2 production. The highest HPR reported to date of 12.4 L H2 /L-d at 4-h HRT using tequila vinasse. Microbial resistance and resilience were keystone for efficient H2 production. Clostridium spp. and lactic bacteria seem to be key in inducing ecosystem stability. Abstract: The performance and microbial communities of a continuous dark fermentation reactor exposed to perturbations induced by substrate change and acidic pH shock were investigated. A mesophilic well-mixed reactor separately fed with two types of tequila vinasses (TVs) and lactose was operated at a fixed pH of 5.5, except during short-term pH (3.8) stress, for ~61 days at decreasing hydraulic retention times (HRTs) from 24 to 4 h. During the first ~23 days of operation with TV, a decrease in HRT down to 4 h resulted in the highest reported biohydrogen productivity from TV of 12.4 NL/L-d. It was shown that abrupt change in TV type (even with temporal feeding of lactose) and transient over-acidification impaired the normal operation of the reactor. However, it rapidly recovered from such disturbances, sustaining similar high-rate productivity to that previously encountered. Recovery was attributed to resistant and resilient microbial community features, as supported by molecular characterisation.